Beyond the Banks: paving the way for environmental flows in Nepal - Tachamo-Shah, R. D.; Nepal, Santosh; Shah, D. N.; Eriyagama, Nishadi (Elsevier, 2025)
Nepal has huge hydropower potential. Although the concept of environmental flows (e-flows) emerged in the early 2000s, its integration into hydropower development remains in the early stages. This study represents the first comprehensive effort to evaluate key stakeholders’ awareness of e-flows and identify the major challenges hindering their mainstream adoption in Nepal’s hydropower sector. Furthermore, it documents stakeholders’ perceptions regarding the impact of hydropower development on aquatic biodiversity and river ecology. An extensive survey was conducted between December 2022 and January 2023, collecting responses from a diverse group of stakeholders, including government agencies, water resource developers, user groups, practitioners, researchers, and academics. Additionally, focus group discussions were held in the Karnali River basin of western Nepal. The findings reveal that only 50 % of respondents are familiar with the e-flows concept. However, 80 % believe that e-flows have not been adequately implemented in any existing hydropower projects in the country. Similarly, 72 % of respondents perceive that hydropower development leads to biodiversity loss, while 56 % believe it reduces downstream water flow. The key challenges identified include (a) inadequate follow-up on environmental impact assessments (EIAs), (b) weak regulatory enforcement, (c) insufficient civil society oversight for ensuring compliance with EIA recommendations, (d) limited technical expertise, and (e) the absence of user-friendly e-flow estimation methods. The study’s findings provide valuable insights for policymakers to promote sustainable water resources development and mitigate the ecological impacts of hydropower projects.